A combined approach for weak fault signature extraction of rolling element bearing using Hilbert envelop and zero frequency resonator. (14th April 2018) - Kumar, Keshav; Shukla, Sumitra; Singh, Sachin Kumar
Abstract: Periodic impulses arise due to localised defects in rolling element bearing. At the early stage of defects, the weak impulses are immersed in strong machinery vibration. This paper proposes a combined approach based upon Hilbert envelop and zero frequency resonator for the detection of the weak periodic impulses. In the first step, the strength of impulses is increased by taking normalised Hilbert envelop of the signal. It also helps in better localization of these impulses on time axis. In the second step, Hilbert envelope of the signal is passed through the zero frequency resonator for the exact localization of the periodic impulses. Spectrum of the resonator output gives peak at the fault frequency. Simulated noisy signal with periodic impulses is used to explain the working of the algorithm. The proposed technique is verified with experimental data also. A comparison of the proposed method with Hilbert-Haung transform (HHT) based method is presented to establish the effectiveness of the proposed method. Highlights: Hilbert envelop and Zero frequency resonator based algorithm is developed for the early detection of bearing faults. The proposed technique is compared with the Hilbert-Haung transform based identification of bearing faults. The proposed technique gives a single dominant peak at fault frequency.